Differential expression of duplicated binary toxin genes binA/binB in Lysinibacillus sphaericus C3‐41. (31st May 2017) - Fu, P.; Xiang, X.; Ge, Y.; Yuan, Z.; Hu, X.
Abstract: Due to the self‐produced binary toxins BinA/BinB, some Lysinibacillus sphaericus isolates exhibit high toxicity against mosquito larvae and are utilized in mosquito control programmes. Previous whole‐genome sequencing revealed the presence of a large plasmid pBsph in L. sphaericus C3‐41, which contains a 30·5‐kb duplication of the genome including the binary toxin genes binA / binB . This was confirmed by Southern blot and qPCR experiments in this study. Mutants of L. sphaericus C3‐41, bearing disruptions of the chromosomal‐bin (C3‐41ΔCab ) or the plasmid‐bin (C3‐41ΔPab ) and a plasmid‐cured strain G725, were generated. It was observed that the three mutants, especially that of C3‐41ΔPab and G725, had lower mRNA level from the early to middle sporulation phase and expressed less binary toxin during the whole sporulation phase. The mosquitocidal activity of the wild strain against 4th instar Culex quinquefasciatus larvae determined by LC50 displayed about 4, 15 and 35 times higher than that of C3‐41ΔCab, C3‐41ΔPab and G725 respectively. These results suggest that both chromosomal‐ and plasmid‐borne bin genes, especially the latter, contribute to the full toxicity of the wild strain. The study provides an important clue for the evolution and application of mosquitocidal L. sphaericus . Significance and Impact of the Study: This study provides the first empirical evidence that Lysinibacillus sphaericus C3‐41 has chromosomal‐ and plasmid‐borne bin operon and both are necessary for full toxicity against mosquito larvae, of which the plasmid‐borne one contributes more to the production and activity of the binary toxin than the chromosomal‐born one. The study provides an important clue for the evolution and application of mosquitocidal L. sphaericus . Abstract : Significance and Impact of the Study: This study provides the first empirical evidence that Lysinibacillus sphaericus C3‐41 has chromosomal‐ and plasmid‐borne bin operon and both are necessary for full toxicity against mosquito larvae, of which the plasmid‐borne one contributes more to the production and activity of the binary toxin than the chromosomal‐born one. The study provides an important clue for the evolution and application of mosquitocidal L. sphaericus .